Acute Trauma and Trauma Care in Orthopedics (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
Orthopedics and trauma surgery are clinically challenging areas involving the treatment of injuries and related diseases of the musculoskeletal system, which can be caused by trauma, accidents, sports injuries, degenerative and congenital diseases, infections, and tumors. We have witnessed developments in all aspects of orthopedic surgery, such as the use of both invasive procedures and non-invasive and non-surgical methods to correct and treat disease. Common orthopedic problems include knee osteoarthritis, spinal deformities, and a variety of different sports injuries. Since these health conditions can greatly affect a person's quality of life, it is important for patients to receive a high level of treatment from an experienced physician. Consequently, there is also an increasing need for interdisciplinary treatment strategies, as these patients often present with underlying comorbidities that could have led to the injury itself, and thus require specific treatment regimens. This Special Issue combines original research and review papers, with a focus on the recent advances in orthopedics and trauma surgery.